“La huella troyana en las continuaciones del Amadís de Gaula” - José, Emilio (Troianalexandrina, 2006)
Abstract Castilian “libros de caballerías” of the sixteenth century are a good example of the survival of the Trojan legend in peninsular literature. Its presence is found in Rodríguez de Montalvo’s Amadís de Gaula. But those books belonging to the Amadisian family also have recourse to the characters and well-known episodes of this tradition. In these chivalrous sequels, writers choose the most famous Greek and Trojan characters’ deeds or love affairs as a term of contrast in order to emphasize their own characters’ superiority. Well-known creatures, such as Medea, added to Trojan subject-matter by medieval writers, Achilles or Pantasilea appear in Renaissance stories of chivalry in wonderful adventures and in episodes with a remarkable allegorical value. Although their narrative function may be considered a secondary one, there are some chivalry books which repeat again the conflict between Greeks and Trojans arising from Helena’s kidnapping. If Castilian authors of the sixteenth century give an account of their literary culture by rescuing past classical and medieval topics, the Trojan legend finds in the chivalry genre an ideal way to gain renewed diffusion.